Factors That Influence the Uptake of an M-Pesa Security System among Mpesa Agents In Nairobi County - Sichangi, Irene Sitawa (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates factors influencing the adoption of an enhanced M-PESA security system among agents in Nairobi County, amidst growing concerns about vulnerabilities in mobile payment systems. With mobile commerce thriving globally, particularly in developing regions, the integration of robust security measures becomes paramount. The focus on M-PESA, a dominant player in the mobile money market, suggests the urgency of fortifying transactional security to prevent fraud and unauthorized access, challenges accentuated by the reliance on basic authentication methods like PINs. Utilizing the Technology Acceptance Model (TAM) as the theoretical framework, this research examines the impact of perceived vulnerability, response cost, response efficacy, self-efficacy, and both intrinsic and extrinsic rewards on security system uptake. The methodology involved a predictive correlational study design, gathering data from 375 M-PESA agents in Nairobi via structured questionnaires, ensuring a representative sample through a clustered sampling approach. Regression analysis was employed to quantify the influence of each factor. Results indicate that perceptions of vulnerability and personal confidence (self-efficacy) in handling security measures significantly predict the willingness to adopt enhanced security solutions. Interestingly, intrinsic rewards influenced adoption positively, reflecting a motivation rooted in personal satisfaction and responsibility, while extrinsic rewards and perceived response efficacy showed no significant impact. These findings suggest that enhancing M-PESA agents' self-efficacy and addressing their perceived vulnerabilities could be more effective than offering external incentives.